Allopurinol Ameliorates Thioacetamide-Induced Acute Liver Failure by Regulating Cellular Redox-Sensitive Transcription Factors in Rats - Demirel, Ulvi; Yalniz, Mehmet; Aygun, Cem; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Kazım; Bahcecioglu, Ibrahim Halil (Springer/Plenum Publishers, 2012)
Oxidative stress plays important role in the development of acute liver failure. In this study, we investigated effects of allopurinol (AP) upon thioacetamide (TAA)-induced liver injury and the potential mechanisms leading to amelioration in inflammation with AP treatment. Acute liver failure was induced by intraperitoneal administration of TAA (300 mg/kg/day for 2 days). Thirty-five rats were divided into five groups as control (group 1), TAA (group 2), TAA + 25AP (group 3), TAA + 50 AP (group 4), and TAA + 100AP (group 5). The number of animals in each group was seven. At the end of the study, histopathological, biochemical, and western blot analysis were done. TAA treatment significantly increased serum levels of aminotransferases, liver malondialdehyde (MDA), nuclear factor-kappa B (NF-O > B ), activator protein-1 (AP-1), tumor necrosis factor-alpha (TNF-alpha), cyclooxygenase-2 (COX-2) and interleukin-6 (IL-6) levels, and the necro-inflammation scores. Nevertheless, nuclear factor E2-related factor-2 and heme oxygenase-1 (HO-1) expressions in the liver were decreased by TAA. AP treatment significantly lowered the serum levels of aminotransferases (P < 0.01) and liver MDA, NF-kappa B, AP-1, TNF-alpha, COX-2, and IL-6 expressions (P < 0.05). Moreover, AP restored the liver Nrf2 and HO-1 expressions and improved the necro-inflammation scores significantly. AP improves oxidative stress-induced liver damage by regulating cellular redox-sensitive transcriptor factors and expression of pro-inflammatory and antioxidant defense mechanisms. AP probably exerts these beneficiary features by its free radical scavenging ability in a dose-dependent manner.
Keywords: oxidative stress; allopurinol; liver; redox-sensitive transcription factors; thioacetamide